'I Want to Live, I Want to Draw': The Poetics of Drawing and Graphic Medicine. (July 2018) - Venkatesan, Sathyaraj; Peter, Anu Mary
Accredited as the provenance of creative art and appreciated for its verisimilar mimetic virtues, drawing is a cathartic form of visual art. Specifically, the curative utility of drawing is anchored on its multifaceted health-enhancing qualities. Drawing is often practised either as a technique of narration, as in visual communication, or as a therapeutic exercise, as in clinical contexts. Interestingly, in the field of graphic medicine, which is a productive intersection of comics and medicine, drawing is practised both as a narrative technique as well as a mode of therapy. Analysing scenes of drawing in selected graphic medicine memoirs such as David Small's Stitches: A Memoir (2009, New York: W.W. Norton & Co) and Katie Green's Lighter than My Shadow (2013, London: Random House), this article investigates how these graphic medical narratives offer an insight into the healing potentials of drawing. This article uses the term 'drawing' in two distinct yet interrelated senses: one is the process of drawing which denotes the depiction of the artist himself/herself involved in the act of drawing, and the other is the end product of drawing such as the picture/image or painting. By elaborating the psychological benefits of drawing, the article also brings into relief how the act of drawing facilitates self-reclamation by assisting patients or traumatized individuals in resolving their chaos through creative expression.